Evaluasi Pertumbuhan Tanaman Eukaliptus (Eucalyptus sp) Pada Variasi Umur dan Unit Pengelolaan Tanah yang Berbeda - Sugeng Wahyudiono; M. Darul Falah; Siman Suwadji; Katharina Sari Narulita Aeng (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2022)
Eucalyptus sp is a type of exotic plant that is cultivated in Riau Fiber. Particularly in terms of soil, this Eucalyptus species was developed in soil management unit B and soil management unit C. Differences in variations in plant growth in the two land management units are not known with certainty because there is no accurate information. This research was conducted at the East Teso Estate which is one of the forest management units of Riau Fiber which included measuring tree height with variations in age of 6 months, 12 months and 18 months, as well as tree diameter and calculating the percentage of single trees with variations in age of 12 months and 18 months. in the land management unit B and soil management unit C which were tested using the t-test at a test level of 5%. The results showed that height growth had a significantly different effect on the two soil management units, namely 4.39 m in soil management unit B and 3.62 m in soil management unit C at 12 months of age and 6.43 m in soil management unit B and 5.87 m in soil management unit C at 18 months old. As for plant height at 6 months, diameter and percent of single trees aged 12 months and 18 months, the results were not significantly different in soil management unit B and soil management unit C.